2006
DOI: 10.1111/j.1365-2133.2006.07171.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ultraviolet (UV) transmission by emollients: relevance to narrowband UVB phototherapy and psoralen plus UVA photochemotherapy

Abstract: This study has revealed considerable variability in the practice of emollient use before phototherapy treatments. Although the majority of centres included in this study did not routinely use emollients, almost one third did. Our in vitro measurement of 30 emollients revealed marked variation in UV transmission, with many emollients blocking sufficient UV to affect the response to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
(35 reference statements)
0
21
0
Order By: Relevance
“…These results suggest that prophylactic administration of treated donor lymphocytes may be an ideal method of enhancing posttransplant immunity in recipients of allogeneic BMT: a method of adoptive cellular immunotherapy that avoids the thymic damage associated with GVHD while producing a protective antiviral effect. Photo-activated amotosalen-DNA crosslinked treatment of T cells is an established treatment process that has already been used in human to treat cutaneous T cell lymphoma, GvHD, and autoimmune disease (53)(54)(55). The present data demonstrating the antiviral activity and lack of toxicity following prophylactic adoptive cellular immunotherapy using amotosalen-treated donor lymphocytes suggests that clinical trials of this approach in patients undergoing allogeneic BMT may be warranted.…”
Section: Discussionmentioning
confidence: 75%
“…These results suggest that prophylactic administration of treated donor lymphocytes may be an ideal method of enhancing posttransplant immunity in recipients of allogeneic BMT: a method of adoptive cellular immunotherapy that avoids the thymic damage associated with GVHD while producing a protective antiviral effect. Photo-activated amotosalen-DNA crosslinked treatment of T cells is an established treatment process that has already been used in human to treat cutaneous T cell lymphoma, GvHD, and autoimmune disease (53)(54)(55). The present data demonstrating the antiviral activity and lack of toxicity following prophylactic adoptive cellular immunotherapy using amotosalen-treated donor lymphocytes suggests that clinical trials of this approach in patients undergoing allogeneic BMT may be warranted.…”
Section: Discussionmentioning
confidence: 75%
“…1,3,5,18,19 Two studies 3,5 showed that UV transmission may be enhanced by emollients while two reported the contrary, 1,18 with Otman et al 1 concluding that, in the NB-UVB range, 23 of 30 emollients had a monochromatic protection factor (MPF) of 1AE2 or above -a result considered clinically significant in order to avoid a decrease of UV transmission. 1,3,5,18,19 Two studies 3,5 showed that UV transmission may be enhanced by emollients while two reported the contrary, 1,18 with Otman et al 1 concluding that, in the NB-UVB range, 23 of 30 emollients had a monochromatic protection factor (MPF) of 1AE2 or above -a result considered clinically significant in order to avoid a decrease of UV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Equally, Hudson-Peacock et al [45] found a reduction in MED by 16% for mineral oil. Conversely, Behrens-Williams et al [46] found that an emulsion containing 35% mineral oil, 30% cetylstearyl alcohol and vaseline had no effect on UVB-induced erythema, and Otman et al [47] found that a variety of mineral oil-containing emulsions decreased the sensitivity to UV, but it should be realized that these formulations also contained soft paraffin waxes. The consensus of evidence of the effects of UV irradiation and mineral oil in humans is that mineral oil has a slight, reducing effect on the MED of skin of an order similar to that of glycerol because of its refractive index.…”
Section: Mineral Oil: Uvb Irradiation and Photocarcinogenesismentioning
confidence: 99%